The Moderating Effect of Religiousness and Spirituality on the Relation Between Dyadic Sexual and Non-Sexual Communication with Sexual and Marital Satisfaction Among Married Jewish Women - Lazar, Aryeh (Archive for the psychology of religion, 2016)
Moderating effects of religiousness and spirituality on the relations between sexual and non-sexual dyadic communication with sexual and marital satisfaction were examined. Three hundred forty-two married Jewish women responded to self-report measures. Religiousness moderated the relations between both sexual and non-sexual communication with marital satisfaction—for the less religious these relations were stronger in comparison with the more religious—but not with sexual satisfaction. Sexual communication had a unique contribution to the prediction of sexual satisfaction while both types of communication demonstrated unique contributions to the prediction of marital satisfaction. The implications of these findings on the role of dyadic communication in relational satisfaction and the meaning of sexual and marital satisfaction for the more and less religious are discussed.